Assessment of OTEC Potentiality in the Niger Delta and Lagos State Coastal Regions of Nigeria - Emughiphel Nelson Igoma (International Journal of Advances in Engineering and Management (IJAEM), 2025)
The gap arises as a result of the high usage together with the electricity generation, which has caused everyday epileptic power supply and dependence of stand-in electric generators that restrict productivity. Energy assurance concerns loom in the future as a result of the decrease in the production of domestic oil. Therefore, pursuing renewable source of energy like OTEC, which deals with ocean thermal gradients, can give reliable, clean energy to ameliorate the power generation. Precisely, in order to bring investment of OTEC in the Niger Delta and Lagos State coastal regions, the assessment of OTEC potentiality in these regions has been conducted. Accordingly, the work looked at the OTEC potentiality along the Niger Delta and Lagos State Coastal cities like Brass, Bonny, Burutu, Calabar, Ebute-Ikorodu, Esuk-Oron, Lagos, Okirika, and Port Harcourt respectively. The results show that the minimum average approximate monthly hot seawater temperatures of these areas considered are between 250C and 270C and a cold seawater depth of around 800m to 1000m, which translates to an approximate average cold seawater temperatures of between 50C and 60C representing 200C differential temperature thereby displaying OTEC potentiality in these regions. That means the investment of OTEC is possible.
Keywords: Assessment; OTEC; Potentiality; Niger Delta; Lagos State; Coastal Regions; Nigeria.